ERGONOMIC RISK ANALYSIS AND MUSCULOSKELETAL DISORDERS (MSDs) OPERATOR FINAL INSPECTION ON AUTMOTIVE INDUSTRY IN TANGERANG CITY - Mariyatul Qibtiyah; Januar Ariyanto; Triana Srisantyorini; Aragar Putri; Agus Triyono (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Ergonomics is very important to note so that work-related illnesses and accidents do not occur. Disturbances arising from ergonomics are Musculoskeletal disorders (MSDs), namely disorders of body structures such as muscles, joints, tendons, ligaments, nerves, cartilage, bones, local blood circulation system. Ergonomics risks were identified using REBA and MSDs complaints using the Nordic Body Map questionnaire. Age, education, exercise habits, smoking habits, BMI, body posture and length of work are factors that can influence MSDs complaints. The aim of this research is to know the factors that influence MSDs complaints. Cross sectional study design with a sample of 231 using logistic regression analysis. The results showed that the ergonomic risk level was low 17,3%, medium 16,9% and high 65,8%. The prevalence of MSDs complaints is 65,8% felt by operators. Respondents aged > 35 years (42,9%), SMA/SMK and below (91,8%), do not have exercise habits 95,2%, smoke every day (59,3%), BMI is overweight (72,7%), risky posture (83,1%) and normal working hours (72,7%). There is a relationship between ergonomic risk, body posture and MSDs complaints. In conclusion, the dominant factor influencing MSDs complaints is body posture with OR 0,127. The research suggestion is to make improvements through the OHS control hierarchy such as equipping lifting equipment, re-designing conveyors for transporting tires, modifying racks to be non-level, socializing working safely and working with poster zones, making work procedures safe.